2002
DOI: 10.1183/09031936.02.01612001
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation-induced activation of the mitogen-activated protein kinase pathway

Abstract: Mechanical ventilation of patients can be a life-saving treatment, but also imposes additional stress on the lung. Mitogen-activated protein kinases (MAPK) represent a family of protein kinases that become phosphorylated and activated by many different forms of stress.Using Western blot analysis, the present study analysed the effects of high distending pressure ventilation on the activation of the MAPK extracellular signal-related kinases (ERK)-1/2, c-Jun amino-terminal kinases (JNK) and p38 kinase, and on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 40 publications
5
77
0
1
Order By: Relevance
“…[7][8][9][10][11]18 Our results further show that up-regulation of JNK, p38 MAPK, NF-KB, and caspase-3 is associated with inflammation and apoptosis in VILI; up-regulation of ERK is not associated with VILI.…”
Section: Mechanical Ventilation With High V T Results In Vilisupporting
confidence: 62%
See 1 more Smart Citation
“…[7][8][9][10][11]18 Our results further show that up-regulation of JNK, p38 MAPK, NF-KB, and caspase-3 is associated with inflammation and apoptosis in VILI; up-regulation of ERK is not associated with VILI.…”
Section: Mechanical Ventilation With High V T Results In Vilisupporting
confidence: 62%
“…8 Animal studies have demonstrated that high V T ventilation leads to increased neutrophil infiltration, activation of inflammatory cytokines, pulmonary inflammation, and diffuse alveolar damage via activation of the mitogen-activated protein kinase (MAPK) and nuclear factor kappa B (NF-KB) pathways. 9 Thus, VILI in animal models resembles the clinical features of ARDS. 10,11 Hyperventilation of a single lung in an isolated rat lung model leads to production of pro-inflammatory tumor necrosis factor alpha, increased permeability, and injury to the contralateral lung via circulating mediators, that is, biotrauma.…”
Section: Introductionmentioning
confidence: 97%
“…Ventilation leading to the nuclear translocation of NF-kB has been previously shown in cell culture, 41 in isolated perfused rat lungs, 42 and in animal lung injury induced by ventilation. 43 In this study, the activation of NF-kB was markedly attenuated by HCA accompanied by the reduction of oxidative stress from neutrophil-mediated injury. It has also been reported that hypercapnic acidosis inhibits the adhesion of endotoxin-induced neutrophils to pulmonary endothelial cells through attenuating IkB-a degradation, which in turn neutralizes the DNA-binding activity of NF-kB.…”
Section: Discussionmentioning
confidence: 53%
“…Transcriptional modulation by MV is supported by several published studies, which show that stretching lung-derived cells in vitro activates transcription factors, which promote proinflammatory cytokine transcription (19 -21). Activation of the transcription factors NF-B and AP-1 occurs when lungs are ventilated ex vivo and in vivo with moderate to large tidal volumes (5,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…The role of GADD45 up-regulation in the pathogenesis of ALI is unknown; however, one function of GADD45 is to activate MEKK4, which in turn is an upstream regulator of JNK MAPK. JNK phosphorylates and activates members of the AP-1 family of transcription factors and has been implicated in ventilator-induced lung injury (23,28). Thus, it is a biologically plausible hypothesis that GADD45 may contribute to the pathogenesis of ALI, and further research into its role is warranted.…”
Section: Discussionmentioning
confidence: 99%